Occupational health and safety-oriented medical waste management: A case study of Istanbul - Eren, Emre; Tuzkaya, Umut Rifat (SAGE PUBLICATIONS LTD, 2019)
The outstanding pace of technological development around the world coupled with increasing population and rapid urbanization have brought along an ever-increasing demand for healthcare services. This trend results in an increasing amount and variety of medical wastes. Accordingly, the issue of effective collection, transportation and disposal of medical wastes, specifically in large cities, has become a critical concern from the viewpoint of urban logistics and holds great importance in terms of safety. This study aims to determine the safety of hospitals in their medical waste management function. The study involves the determination of medical waste management steps, establishment of a hierarchical structure, and weighting of the criteria within the established hierarchical structure by means of the analytic hierarchy process method. Afterwards, the extent to which these criteria are adopted in hospitals was evaluated by the medical waste management officers of those hospitals, and safety scores were obtained for each hospital by associating the results with the weighted values obtained by the analytic hierarchy process method. The model proposed for medical waste management problems encountered by healthcare institutions in Istanbul was implemented for a specific region of Istanbul province, and the obtained results were analyzed. Evaluation of the opinions of the healthcare officials for determination of the medical waste management safety scores showed that the collection criterion has significantly higher importance than the temporary storage and transportation criteria. The effect on hospital personnel sub-criterion of the collection criterion had the highest score. This revealed the importance of the collection process that takes place between storage and transportation, for evaluating the human waste-based risks.
Keywords: Medical waste; healthcare waste; medical waste logistics; medical waste management; analytic hierarchy process; safety scores; MULTICRITERIA DECISION-MAKING; RISK ANALYSIS; DISPOSAL; AHP; GENERATION; SELECTION; Engineering; Environmental Sciences & Ecology